Multicentric Castleman's Disease in a Hepatitis C-Positive Intravenous Drug User: A Case Report - D. Y. Talukder; S. N. Delpachitra (Case Reports in Medicine)
Introduction. We report a rare presentation of Castleman's disease in a hepatitis C-positive patient and present a short review of treatments described in other similar case reports and studies. Case Presentation. A 46-year-old male with untreated hepatitis C and a 16-year history of intravenous drug use presented with pleuritic chest pain and bony pain in the knee, hip, and lower back, on a background of unexplained weight loss of 40 kilograms, fevers, night sweats, and repeated infections over the last two years. Examination discovered tender hepatomegaly, a warm right knee effusion, and painless lymphadenopathy. The patient was reactive to Epstein Barr virus and cytomegalovirus; however, HIV and HHV-8 viral testing was negative. Osteomyelitis of vertebrae T8–T11 and septic arthritis of the knee were found on investigation. A lymph node biopsy revealed histology suggestive of plasmacytic Castleman's disease. The patient is to commence rituximab treatment. Conclusion. Castleman's disease continues to present in novel ways, which may lead to difficulties in clinicopathologic diagnosis. A growing body of evidence suggests larger studies are required to determine the best treatment for multicentric Castleman's disease, particularly in patients with a concomitant disease, including hepatitis C.